2017
DOI: 10.1002/prot.25287
|View full text |Cite|
|
Sign up to set email alerts
|

Uncovering allostery and regulation in SAMHD1 through molecular dynamics simulations

Abstract: The human sterile alpha motif and HD domain-containing protein 1 (SAMHD1) is a retroviral restriction factor in myeloid cells and non-cycling CD4+ T cells, a feature imputed to its phosphohydrolase activity-the enzyme depletes the cellular dNTP levels inhibiting reverse transcription. The functionally active form of SAMHD1 is an allosterically triggered tetramer which utilizes GTP-Mg -dNTP cross bridges to link and stabilize adjacent monomers. However, very little is known about how it assembles into a tetrame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Two sets of independent trajectories of length 200 and 300 ns each were generated from MD calculations at 295 K for each of the eight monomeric systems. In addition, the trajectories of the wt tetrameric system (with C341 and C350 disulfide linked) that were generated in our previous study were also used for analysis. Here, we selected a particular monomer (chain B) from the tetrameric system for comparison with the other monomeric systems that were investigated in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two sets of independent trajectories of length 200 and 300 ns each were generated from MD calculations at 295 K for each of the eight monomeric systems. In addition, the trajectories of the wt tetrameric system (with C341 and C350 disulfide linked) that were generated in our previous study were also used for analysis. Here, we selected a particular monomer (chain B) from the tetrameric system for comparison with the other monomeric systems that were investigated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…in vivo tetramer‐lifetime biochemical investigations demonstrated that SAMHD1 assembly and activation requires a K m of ~10 μM, which is the dNTP concentration in cycling cells . Our own computational studies shed light on the influence of GTP activators and dNTP substrate on tetramer stability and allosteric pathways within the tetramer . However, this model is applicable only in cycling cells, whereas it is in terminally differentiated cells such as macrophages that SAMHD1 restricts HIV‐1.…”
Section: Introductionmentioning
confidence: 99%
“…An active tetramer, then, is stabilized by four allosteric sites. Each allosteric site contacts three monomers in the structure and contains a dGTP/GTP-Mg 2+ -dNTP bridge [22]. Additional metal ions are chelated by the His167-His206-Asp207-Asp311 quartet in order to correctly orient and polarize the dNTP substrate in the catalytic sites of each monomer.…”
Section: Samhd1 Is a Dntpase Comprised Of An N-terminal Sam Domain Amentioning
confidence: 99%
“…The identification of cell cycle-regulated phosphorylated SAMHD1 resulted in the quest to characterize this post-translational modification and its effect on the tetramerization and activation of SAMHD1. While many groups found that dNTP activators dissociate from the A2 allosteric sites of pSAMHD1, leading to tetramer destabilization and subsequent loss of triphosphohydrolase activity [22,25,35,36], there are conflicting reports stating that the dNTPase activity of pSAMHD1 and phosphomimetic mutants T592E and T592D are very similar to wildtype SAMHD1 [37][38][39][40]. Despite the discrepancies surrounding the dNTPase activity of pSAMHD1, phosphorylation of SAMHD1 has also been shown to play a role in HIV-1 restriction-a function that we will further discuss in later sections.…”
Section: The Dntpase Activity Of Samhd1 Can Be Regulated Via Post-tramentioning
confidence: 99%
“…Oligomerization of SAMHD1 is required for its catalytic dNTPase activity and is induced upon cofactor binding at two allosteric sites within the protein [7][8][9][10][11][12]. At allosteric site 1, dGTP or GTP binding leads to SAMHD1 dimerization, while the subsequent binding of any dNTP to allosteric site 2 induces tetramer formation [1,13,14]. SAMHD1 converts dNTPs into deoxynucleosides (dN) and inorganic triphosphates (PPPi) and thereby counteracts the de novo dNTP synthesis, primarily conducted by ribonucleotide reductase (RNR) and cellular deoxynucleoside kinases, which are mainly active during the S phase of the cell cycle [15][16][17][18].…”
Section: The Dntpase Samhd1mentioning
confidence: 99%